Clinical outcomes of paediatric patients supported by the Berlin Heart EXCOR: a systematic review. (1st April 2019) - Rohde, Sofie; Antonides, Christiaan F J; Dalinghaus, Michiel; Muslem, Rahatullah; Bogers, Ad J J C
Summary: Ventricular assist devices (VADs) are widely accepted as therapy to bridge children to heart transplantation. We provide a systematic review of the current state of clinical outcomes in children after paediatric VAD support by the Berlin Heart EXCOR (BH EXCOR) device. A systematic literature search was performed in April 2018. Studies reporting clinical outcomes in at least 15 children supported by a BH EXCOR VAD were included. Additionally, we focused on outcomes in small children and compared outcomes of children supported by a left ventricular assist device (LVAD) versus children supported by a biventricular assist device (BiVAD). Eighteen publications fulfilled the inclusion criteria and were included in this systematic review. Mortality rates ranged from 6.3% [confidence interval (CI) 0.0–18.1%] to 38.9% (2.8–75.0%) while transplantation rates ranged from 37.0% (CI 18.8–55.2%) to 72.5% (CI 63.9–81.2%) and successful weaning rates from 0.0% to 20.7% (CI 6.0–35.5%). In children under 1 year of age, mortality rates ranged from 20.0% to 55.5% and transplantation rates ranged from 0.0% to 62.5%. BiVAD support seemed to result in worse clinical outcomes than LVAD support. Incidence of stroke ranged from 5.0% to 47.0% in all children supported with the BH EXCOR. Although a high incidence of adverse events such as stroke and pump thrombosis is reported, VAD support should be considered in children with end-stage heart failure awaiting heart transplantation. Further research is warranted, especially on optimal timing of device implantation and anticoagulation regimens.